Micro-computed tomography and histomorphometric analysis of the effects of platelet-rich fibrin on bone regeneration in the rabbit calvarium - ERDEM, NECİP FAZIL (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Objective: The present study aimed to investigate the effectiveness of platelet-rich fibrin (PRF) on bone regeneration when used alone or in combination with hydroxyapatite (HA)/beta-tricalcium phosphate (beta TCP). Design: In this study, 20 New Zealand white rabbits were used and four calvarial defects were prepared in each animal. PEP, Straumann (R) Bone Ceramic (SBC), or PEP + SBC was applied to the defects; one defect was left untreated as a control. Ten rabbits were sacrificed at week 4(T-1) and 10 at week 8 (T-2). After micro-computed tomography (micro-CT) scanning, the samples were sent for histological and histomorphometric analysis to evaluate and compare the volume and area of regenerated bone. Results: Histomorphometric and micro-CT analysis showed that both PEP and SBC significantly increased bone regeneration at T-1 and T-2 (P < 0.01). When PEP was used in combination with HA/beta TCP, a further significant increase in new bone formation was observed at T-1 and T-2 compared with that when PRF or SBC was used alone (P < 0.01). Conclusions: PRF has a positive effect on bone formation when used alone and in combination with HA/beta TCP. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Platelet-rich fibrin; Rabbit; Calvarial defect; Hydroxyapatite; Beta-tricalcium phosphate; TRICALCIUM PHOSPHATE; GROWTH-FACTORS; IMPLANT PLACEMENT; AUTOGENOUS BONE; DEFECTS; PLASMA; PROLIFERATION; AUGMENTATION; COMBINATION; BIO-OSS(R)